Analysis of Variable Bit Rate WH/CI‐Spread OFDM based Integrated Satellite‐Terrestrial Broadcast System. Issue 6 (1st April 2019) - Agarwal, Akash; Kumar, Preetam
Abstract : In this study, the exact closed‐form signal‐to‐interference‐noise ratio (SINR) expression, for the impact of Doppler frequency shift on minimum mean square error receiver is derived for Walsh Hadamard (WH) and polyphase carrier interferometry (CI) code based multicarrier spread orthogonal frequency division multiplexing (SOFDM) transmission scheme over integrated satellite–terrestrial broadcast system. Additionally, bit error rate and spectral efficiency are analysed based on the obtained SINR expression. To examine that, three‐state Fontan land mobile satellite, and six‐path typical urban and rural area terrestrial channel models are employed. This analysis is performed to substantiate variable bit rate (VBR) quality of service at the physical layer of digital video broadcast satellite handheld (DVB‐SH)‐A architecture, the provision of which is absent in DVB‐SH standard. VBR is assumed for SOFDM. The results illustrate that WH‐SOFDM outperforms CI‐SOFDM under both performance measures in all the three channel environments. Further, pilot‐based channel estimation technique is performed and the estimated error variance is evaluated for VBR WH/CI‐SOFDM. Later, block‐wise system computational complexity of WH/CI‐SOFDM schemes is evaluated. It is shown that, CI‐SOFDM is a relatively more complex system than WH‐SOFDM. Thus, a trade‐off is present between the achieved performance gain and system complexity.